Pengaruh Media TAKALINTAR (Tabel Perkalian Pintar) terhadap Kemampuan Berpikir Kritis Siswa pada Materi Perkalian Matematika Kelas IV SD N Wonoyoso - Wulan Anjani; Nimas Puspitasari; Yogi Ageng Sri Legowo (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2024)
This research aims to determine whether or not there is an influence of the use of takalintar media (smart multiplication tables) on students' critical thinking skills in fourth grade Mathematics multiplication material at SD N Wonoyoso. This research uses a quantitative approach with the Quasi Experimental Design method with the research design used The Nonequivalent Control Group Design. The variables in this research are the independent variable with symbol X, namely Takalintar media and the dependent variable with symbol Y, namely critical thinking ability. The population in this study was the fourth grade students at Wonoyoso State Elementary School, totaling 48 students. The sample was selected using purposive sampling involving all class IV, namely class IVA with 24 students as the control class (not receiving treatment) and class IVB with 24 students as the experimental class (receiving treatment). The data collection technique uses tests to measure the critical thinking abilities of class IV students through several tests including validity tests, reliability tests, normality tests and homogeneity tests, then data analysis techniques using the t test. The results of the research show that the calculated t value is greater than the t table (5.468 > 2.01063), so it can be concluded that Ho is rejected and Ha is accepted, which means "There is an influence of Takalintar media on students' critical thinking abilities in mathematics multiplication material for class IV at Wonoyoso State Elementary School.Keywords: Takalintar Media, students' critical thinking ability